Nitrogen fixation in lysimeter-grown grey alder (Alnus incana (L.) Moench.) saplings - influence of nitrogen fertilization - "Ericsson, Tom"; "Rytter, L" (1998)
A lysimeter study was started in order to test if nitrogen fixation as well as biomass production in grey alder plantations (Alnus incana (L.) Moench.) can be stimulated by daily addition of small N doses. One-year-old grey alder saplings were planted in undrained lysimeters, each filled with 200 litres of quartz sand. Water and a low-concentrated balanced nutrient solution were distributed daily via a drip irrigation system. In this paper a complete N budget for the first growing season is presented. The results showed that presence of mineral N in the growth substrate had no beneficial effect on growth during the first growing season. The capacity of the plants to make use of the daily N additions was overestimated in this investigation. Almost twice as much N was added with fertilizers as the amount of N accumulating in the tissues. Consequently, the N concentration in the drainage water increased and the annual rate of Nsub 2-fixation was strongly suppressed, 31 mg N plantsup -1 (1 kg N hasup -1) versus 1700 mg N plantsup -1 (32 kg N hasup -1) in the controls. However, no harmful effect of the elevated soil-N concentration on nodule development could be detected.
Keywords: "09 BIOMASS FUELS"; "NITROGEN FIXATION"; "BIOMASS PLANTATIONS"; "SILVICULTURE"; "FERTILIZERS"; "NUTRIENTS"; "PLANT GROWTH"; "NITROGEN"; "LYSIMETERS"; "DECIDUOUS TREES"